Use of Bio-activators in Goat Manure Fermentation and Effects of Solid Goat Manure-based Fertilizer on Growth and Yield of Sweet Corn - Safitri, Isnin Kurnia; Fahrurrozi, Fahrurrozi; Muktamar, Zainal; Sudjatmiko, Sigit (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
The presence of bio-activators in the decomposition of goat manure determines the nutrient content of the produced solid organic fertilizer. These experiments aimed to ascertain the impacts of several bio-activators on goat manured-based fertilizer’s nutrient content and its effects on the growth and yield of sweet corn. The first experiment, arranged in complete randomized design with three replicates, employed five treatments of bio-activators. The treatments were (1) no bio-activator, (2) cow blood, (3) cow rumen+cow blood, (4) yeast+cow blood, (5) effective microorganism (EM4). The second experiment was a bi-factorial complete randomized block design with three replicates. The first factor was types of bio-activators: (1) no bio-activator, (2) cow blood, (3) cow rumen+cow blood, (4) yeast+cow blood, (5) effective microorganism (EM4), respectively. The second factor was dosage of goat manure-based solid organic fertilizers: (1) 5 Mg ha-1, (2) 10 Mg ha-1, (3) 15 Mg ha-1. The results indicated that goat manure-based fertilizer produced using cow rumen+cow blood bio-activator had the highest nutrient content. The presence of bio-activators in goat manure-based fertilizer increased the weight of sweet corn (husked-ear and unhusked-ear), the length of sweet corn (husked-ear and unhusked-ear), and the weight of husked-ear sweet corn plot-1, but not the sweet corn diameter (husked-ear and unhusked-ear), and sweetness level. Moreover, the use of goat manure-based fertilizer with 5 Mg ha-1 was generally sufficient to support growth and yield of sweet corn. The optimal combination of treatments to enhance sweet corn growth and yield was the interaction between the cow rumen+cow blood bio-activators and dosage of 5 Mg ha-1.